2016
DOI: 10.1097/ta.0000000000001034
|View full text |Cite
|
Sign up to set email alerts
|

Current management of hemorrhage from severe pelvic fractures

Abstract: Prognostic study, level II; therapeutic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
105
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 204 publications
(130 citation statements)
references
References 33 publications
7
105
0
7
Order By: Relevance
“…Moreover a dedicated pelvic orthopedic surgeons can improve ( p  = 0.004) the number of patients that undergoing definitive unstable pelvic fractures repair with a consequently improvement in outcome [5]. Similar data about the importance of the adherence to defined guidelines have been reported by Balogh et al [16] and recently confirmed by the multi-institutional trial by Costantini et al [10]. …”
Section: Methodsmentioning
confidence: 60%
See 2 more Smart Citations
“…Moreover a dedicated pelvic orthopedic surgeons can improve ( p  = 0.004) the number of patients that undergoing definitive unstable pelvic fractures repair with a consequently improvement in outcome [5]. Similar data about the importance of the adherence to defined guidelines have been reported by Balogh et al [16] and recently confirmed by the multi-institutional trial by Costantini et al [10]. …”
Section: Methodsmentioning
confidence: 60%
“…Ten to fifteen percent of patients with pelvic fractures arrive to the ED in shock and one third of them will die reaching a mortality rate in the more recent reports of 32% [10]. The causes of dying are represented in the major part by uncontrolled bleeding and by patient’s physiologic exhaustion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pelvic fractures patterns included APC III (29), LC II (26), LC III (20), APC II (20), LC I (13), vertical shear (14), APC I (4) and CM (2). Of these, 18 patients had open pelvic fractures.…”
Section: Resultsmentioning
confidence: 99%
“…The most recent analysis, a multicenter observational study by the American Association for the Surgery of Trauma (AAST), reported a 32% mortality rate for complex pelvic fracture patients who presented in shock (14). The majority of trauma centers in that study, and in the United States, emphasize angioembolization (AE) for primary hemorrhage control (1416). While angioembolization is effective in controlling arterial sources of hemorrhage, it does not address the venous or bony hemorrhage within the pelvis (17).…”
Section: Introductionmentioning
confidence: 99%